Ethnicity and displacement in multicultural societies: looking for the roots in M.G.Vassanji’s The Magic of Saida - Abbas, Hussein Ali; Mani, Manimangai (Center for Resource, Research and Publication Services, 2018)
The return of immigrants from the Western countries into the country of origin is increasingly becoming a dominant theme in Canadian ethnic fiction. This article seeks to attribute this return to the multiculturalism, a system that identifies immigrants upon their ethnicities, race in specific. Once the immigrants have problems with ethnicity, they feel they are unrecognized, and their existence in Canada does not make sense. This feeling takes them back into the country of origin to explore their ethnic background. These critical ideas are to be discussed in the light of events and characters of The Magic of Saida by the Canadian M. G. Vassanji. This research intends to show the difficulties faced by people who are born to parents from mixed race.